It is currently 23 Sep 2017, 15:17

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

For which of the following functions is g(c-d) = g(c) - g(d)

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

1 KUDOS received
Intern
Intern
avatar
Joined: 25 Dec 2012
Posts: 28

Kudos [?]: 28 [1], given: 10

For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 11 Feb 2013, 10:09
1
This post received
KUDOS
8
This post was
BOOKMARKED
00:00
A
B
C
D
E

Difficulty:

  35% (medium)

Question Stats:

72% (01:14) correct 28% (01:22) wrong based on 379 sessions

HideShow timer Statistics

For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = \(\sqrt{3x}\)
D g(x) = 5x
E g(x) 15/x


Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those... :x
[Reveal] Spoiler: OA

Kudos [?]: 28 [1], given: 10

5 KUDOS received
Manager
Manager
avatar
Joined: 09 Feb 2013
Posts: 121

Kudos [?]: 1112 [5], given: 17

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 11 Feb 2013, 10:18
5
This post received
KUDOS
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?
A g(x) = x^3
B g(x) = x+5
C g(x) = \(\sqrt{3x}\)
D g(x) = 5x
E g(x) 15/x

Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those... :x


This problem arises because in such type of questions the original function is not given. Instead, we have to find a function which can satisfy the constraint mentioned in the question.
Constraint--> g(c-d) = g(c) - g(d)--->(1), where (c-d), c, d are the values of x.
I am directly putting the value in the answer. You can verify the incorrect option by yourself.

Function as per option D is --->g(x) = 5x
Put the value of x = (c-d), we get --->g(c-d) = 5 (c-d) = 5c - 5d----(LHS)
Put the value of x = c, we get --->g(c) = 5 (c) = 5c ----(RHS)
Put the value of x = d, we get --->g(d) = 5 (d) = 5d----(RHS)

Equate RHS & LHS we get--> 5c - 5d = 5c - 5d
Thus equal.

So the answer is D.

Emma
_________________

Kudos will encourage many others, like me.
Good Questions also deserve few KUDOS.

Kudos [?]: 1112 [5], given: 17

Manager
Manager
User avatar
Joined: 24 Sep 2012
Posts: 90

Kudos [?]: 159 [0], given: 3

Location: United States
Concentration: Entrepreneurship, International Business
GMAT 1: 730 Q50 V39
GPA: 3.2
WE: Education (Education)
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 16 Feb 2013, 13:21
In such questions these are the steps I find useful!!

1) The first step is to check whether you could solve the expression stated in the question( in case the expression is too long) or substitute the expression into the solutions in some manner so as to solve it quickly. If so, this is the quickest way out and usually with a little bit of practice, you can start judging whether this step would work or not before you place your pen on the paper to solve the question.

2) The next method is to find whether the solutions can be substituted into the original expression in some way that is fast and quick. This usually takes some time and hence, mostly does not work. However, if the answer options involve numbers instead of expressions, this might work better.

This method is only for those questions in which the answer options and the questions both contain expressions.

3) You could try substitution of base values to confirm.

.
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = \(\sqrt{3x}\)
D g(x) = 5x
E g(x) 15/x


Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those... :x

Kudos [?]: 159 [0], given: 3

Intern
Intern
avatar
Joined: 20 Apr 2013
Posts: 24

Kudos [?]: 5 [0], given: 99

Concentration: Finance, Finance
GMAT Date: 06-03-2013
GPA: 3.3
WE: Accounting (Accounting)
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 30 Apr 2013, 22:54
Why is option C Wrong
\sqrt{3(c-d)} = \sqrt{(3c)}-\sqrt{(3d)}

Kudos [?]: 5 [0], given: 99

Senior Manager
Senior Manager
avatar
Joined: 16 Dec 2011
Posts: 426

Kudos [?]: 230 [0], given: 70

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 30 Apr 2013, 23:08
Rajkiranmareedu wrote:
Why is option C Wrong
\sqrt{3(c-d)} = \sqrt{(3c)}-\sqrt{(3d)}

Option C says g(x) = \(\sqrt{3x}\)

So, g(c-d) = \(\sqrt{c-d}\)
g(c) = \(\sqrt{c}\)
g(d) = \(\sqrt{d}\)

We cannot say that \(\sqrt{c-d}\) = \(\sqrt{c}\) - \(\sqrt{d}\) for all values of c and d
So we cannot say that g(c-d) = g(c) - g(d) for all values of c and d.

Thus, option c is wrong.

Kudos [?]: 230 [0], given: 70

1 KUDOS received
Manager
Manager
avatar
Joined: 04 Mar 2013
Posts: 87

Kudos [?]: 10 [1], given: 6

Location: India
Concentration: General Management, Marketing
GPA: 3.49
WE: Web Development (Computer Software)
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 04 Jul 2013, 19:48
1
This post received
KUDOS
1
This post was
BOOKMARKED
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = \(\sqrt{3x}\)
D g(x) = 5x
E g(x) 15/x


Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those... :x



put c = 3 and d = 2 or directly substitute c and d

we get option D, :)

Kudos [?]: 10 [1], given: 6

GMAT Club Legend
GMAT Club Legend
User avatar
Joined: 09 Sep 2013
Posts: 17624

Kudos [?]: 271 [0], given: 0

Premium Member
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 14 Jan 2015, 01:30
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

GMAT Books | GMAT Club Tests | Best Prices on GMAT Courses | GMAT Mobile App | Math Resources | Verbal Resources

Kudos [?]: 271 [0], given: 0

Expert Post
5 KUDOS received
EMPOWERgmat Instructor
User avatar
P
Status: GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Joined: 19 Dec 2014
Posts: 9814

Kudos [?]: 3318 [5], given: 171

Location: United States (CA)
GMAT 1: 800 Q51 V49
GRE 1: 340 Q170 V170
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 14 Jan 2015, 23:50
5
This post received
KUDOS
Expert's post
2
This post was
BOOKMARKED
Hi All,

In these types of "function" questions, you can TEST VALUES (especially really simple ones) to find the correct answer.

Let's TEST...
C = 2
D = 1

The question asks us to find the equation that gives us the same result when...

g(2-1) = g(1) is calculated

and when

g(2) - g(1) is calculated

Answer A: g(X) = X^3
g(1) = 1^3 = 1
g(2) - g(1) = 2^3 - 1^3 = 8 - 1 = 7
1 does NOT = 7

Answer B: g(X) = X+5
g(1) = 1+5 = 6
g(2) - g(1) = (2+5) - (1+5) = 7 - 6 = 1
6 does NOT = 1

Answer C: g(X) = \sqrt{3X}
g(1) = \sqrt{3}
g(2) - g(1) = \sqrt{6} - \sqrt{3} = \sqrt{3}(\sqrt{2} - 1)
\sqrt{3} does NOT = \sqrt{3}(\sqrt{2} - 1)

Answer D: g(X) = 5X
g(1) = 5(1) = 5
g(2) - g(1) = 5(2) - 5(1) = 10 - 5 = 5
5 DOES = 5

Answer E: g(X) = 15/X
g(1) = 15/1 = 15
g(2) - g(1) = 15/2 - 15/1 = -15/2
15 does NOT = -15/2

Final Answer:
[Reveal] Spoiler:
D


GMAT assassins aren't born, they're made,
Rich
_________________

760+: Learn What GMAT Assassins Do to Score at the Highest Levels
Contact Rich at: Rich.C@empowergmat.com

Rich Cohen

Co-Founder & GMAT Assassin

Special Offer: Save $75 + GMAT Club Tests Free

Official GMAT Exam Packs + 70 Pt. Improvement Guarantee
www.empowergmat.com/

***********************Select EMPOWERgmat Courses now include ALL 6 Official GMAC CATs!***********************

Kudos [?]: 3318 [5], given: 171

SVP
SVP
User avatar
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1854

Kudos [?]: 2525 [0], given: 193

Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 21 Jan 2015, 20:59
A g(x) = x^3

Power of "x" is changed, so IGNORE

B g(x) = x+5

"x" is added by constant, so IGNORE

C g(x) = \sqrt{3x}

Power of "x" is changed, so IGNORE

D g(x) = 5x

"x" is multiplied by constant 5, so required result is true


E g(x) 15/x

\(\frac{15}{x} = 15 * x^{-1}\)

Again power of "x" is changed, so IGNORE

Answer = D
_________________

Kindly press "+1 Kudos" to appreciate :)

Kudos [?]: 2525 [0], given: 193

GMAT Club Legend
GMAT Club Legend
User avatar
Joined: 09 Sep 2013
Posts: 17624

Kudos [?]: 271 [0], given: 0

Premium Member
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 20 Jun 2016, 03:32
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

GMAT Books | GMAT Club Tests | Best Prices on GMAT Courses | GMAT Mobile App | Math Resources | Verbal Resources

Kudos [?]: 271 [0], given: 0

GMAT Club Legend
GMAT Club Legend
User avatar
Joined: 09 Sep 2013
Posts: 17624

Kudos [?]: 271 [0], given: 0

Premium Member
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 19 Jul 2017, 19:01
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

GMAT Books | GMAT Club Tests | Best Prices on GMAT Courses | GMAT Mobile App | Math Resources | Verbal Resources

Kudos [?]: 271 [0], given: 0

Manager
Manager
avatar
B
Joined: 18 Jun 2017
Posts: 61

Kudos [?]: 2 [0], given: 166

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 18 Aug 2017, 01:01
Plug in values as c=4 and d=2
which will bring down the funtion in problem statement to g(2)=g(4)-g(2).
Now substituting the values in the option available as per the above equation LHS=RHS is option D.

Kudos [?]: 2 [0], given: 166

Senior Manager
Senior Manager
User avatar
G
Joined: 04 Sep 2015
Posts: 479

Kudos [?]: 72 [0], given: 18

Location: India
WE: Information Technology (Computer Software)
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink]

Show Tags

New post 22 Aug 2017, 11:09
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = 3x−−√3x
D g(x) = 5x
E g(x) 15/x


well its jus asking if they are the same or not, for that just substitute the value and we can find out.
Option D is the corect answer.

Kudos [?]: 72 [0], given: 18

Re: For which of the following functions is g(c-d) = g(c) - g(d)   [#permalink] 22 Aug 2017, 11:09
    Similar topics Author Replies Last post
Similar
Topics:
5 EXPERTS_POSTS_IN_THIS_TOPIC For which of the following functions f is f(x) = f(1-x) for Baten80 15 27 Feb 2013, 03:25
60 EXPERTS_POSTS_IN_THIS_TOPIC For which of the following functions is f(a+b)=f(a)+f(b) for zz0vlb 16 10 Oct 2016, 05:37
289 EXPERTS_POSTS_IN_THIS_TOPIC For which of the following functions f is f(x)=f(1-x) for study 34 18 Jul 2017, 17:37
1 EXPERTS_POSTS_IN_THIS_TOPIC For which of the following functions f(x), is it always true that f(a/ Bunuel 2 16 Oct 2016, 07:36
7 EXPERTS_POSTS_IN_THIS_TOPIC Among the following functions, for which one is guerrero25 8 14 Nov 2015, 13:32
Display posts from previous: Sort by

For which of the following functions is g(c-d) = g(c) - g(d)

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  


cron

GMAT Club MBA Forum Home| About| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.